Acute responses to surgical tubing and biokinetic swim bench interval exercise - Sexsmith, J. R.; Oliver, M. L.; Johnson-Bos, J. M. (Journal of Swimming Research, 1992)
Elite male swimmers(N = 22) performed three sets of five, 60 s repeats at 38 strokes per minute interspersed with 30 s rest intervals using surgical tubing (ST) and a biokinetic swim bench (SB). A five-minute recovery was provided between sets. HR, minute ventilation, and oxygen consumption were measured for the final 30 s of each set. Venous lactate was assessed at rest and four-minutes after the last repeat. Surgical tubing evoked lower HR, ventilation, and oxygen consumption at all measurement times. HR increased for both exercises. HLa was increased for both exercises but was lowest for ST. Power output, oxygen consumption, and ventilation were relatively constant during the three exercise sets. This meant that exercise intensity did not change over the course of either exercise sets. Since those measures were stable, the HR probably increased due to increased blood pressure and thermoregulatory factors, such as skin blood flow and sweating. The different responses to the exercises may be due to their dissimilar force generation requirements, and hence, unique motor unit use (synchronization) and recruitment. For example, a large force is required at the commencement of the pull on the swim bench but is delayed with tubing due to its elastic "give" in the initial pull stages. Also the tubing recovery requires resistance to slow the elastic "snap" back while the bench has only the movement of body parts to control. The bench also employs isometric contraction of the legs and back against the restraining belt. The extra bench factors exercise a greater muscle mass and produce a greater metabolic cost, hence the higher values. Implication. These two exercises are supposed to be beneficial for swimming but each evokes a very different response. Which is the more useful? Is either useful? The different responses mean that both cannot be equally useful to the same degree. If responses are this specific, would not it seem possible that swimming itself is equally specific and UNLIKE either exercise? This study supports the specificity of training principle.